Estimating the Benefits of a Faith-Based Correctional Program - Duwe, Grant (2013)
A recent outcome evaluation of the InnerChange Freedom Initiative (InnerChange), a faith-based prisoner reentry program that has operated within Minnesota's prison system since 2002, showed the program is effective in lowering recidivism. This study extends research on InnerChange by conducting a cost-benefit analysis of the program. Because InnerChange relies heavily on volunteers and program costs are privately funded, the program exacts no additional costs to the State of Minnesota. As a result, this study focused on estimating the program's benefits by examining recidivism and post-release employment. The findings showed that during its first six years of operation in Minnesota, InnerChange produced an estimated benefit of $3 million, which amounts to nearly $8,300 per participant. Much of this benefit stems from costs avoided as a result of the program's impact on reoffending